The Role of Law and Human Rights in the Formation of State Institutions: A Comparative Study of Indonesia and Nigeria - Salmon, Hendrik; Jacob, John Tumba (Universitas Negeri Surabaya, 2025)
An efficient state institution, grounded in law and human rights, serves as the primary pillar for political stability and sustainable development, as evidenced by the comparison between Indonesia and Nigeria, two countries that face similar challenges despite their distinct historical backgrounds. This study aims to examine the role of law and human rights in the development of state institutions in both Indonesia and Nigeria, as well as to identify the similarities and differences in how these principles are applied in each nation. The research uses a normative legal approach, incorporating statutory, conceptual, and comparative methods to assess the regulations, legal concepts, and the application of law and human rights in the formation of state institutions in both countries, utilizing primary, secondary, and tertiary legal materials analyzed qualitatively. The results indicate that law and human rights play a significant role in shaping state institutions in both Indonesia and Nigeria, despite their differing legal systems. Indonesia follows the 1945 Constitution, emphasizing the separation of powers and the establishment of the National Commission on Human Rights (Komnas HAM), while Nigeria operates under the 1999 Constitution with a presidential and federal system, along with the creation of the National Human Rights Commission (NHRC). Both nations encounter common challenges, such as weak law enforcement and social inequality, which impede the effective integration of human rights into governance. As a result, strengthening human rights institutions and implementing structural reforms are essential to achieving more inclusive and equitable governance.